(Re) making trajectories: Eviction, control and power. (August 2015) - Selim, Gehan
Abstract: The City of Cairo's experienced a major shift in its urban planning attitude and practice since the mid 1970s which mostly validated elements of economic planning while neutralizing its social aspects. This ad hoc approach escalated conflict in planning politics over the control of space between tiers of the planning institution and the locals leading to rigorous planning actions among major stakeholders such as eviction and control of spaces. The article examines how institutional claims over space reassembled alternative definitions of quality of life in one of Cairo's oldest quarters, and how ambitious planning schemes were mostly driven by entrepreneurial rather than societal. Based on first-hand interviews and visuals, the article aims to reveal the local's struggle to survive such interventions with attention to their daily negotiations in place.